A comparative study of totally extraperitoneal versus transabdominal preperitoneal repair of inguinal hernias - P. B., Sudarshan; B. S., Sundaravadanan; S., Prabu Shankar (International Surgery Journal, 2017)
Background: The two common procedures which are nowadays commonly performed for laparoscopic repair of inguinal hernia are transabdominal preperitoneal (TAPP) and totally extraperitoneal (TEP) mesh repair. This retrospective study was aimed to compare these two, TAPP and TEP laparoscopic approaches for inguinal hernia repair in terms of various outcomes. Methods: In this retrospective study, we included 50 cases of inguinal hernia who underwent laparoscopic approach of inguinal hernia repair at Saveetha medical college and hospital between 2014 and 2016 for a duration of 3 years. Various parameters including the age, sex of patient, type of hernia, preoperative and post-operative complications, duration of hospital stay was analysed. Results: Of the 50 patients who underwent laparoscopic repair, 26 patients underwent TEP and 24 patients under went TAPP procedure. 31 cases were indirect inguinal hernias and 30 cases were direct inguinal hernias, totalling 61 hernia repairs, as 11 patients had bilateral hernia. One female inguinal hernia and 4 cases of recurrent hernia were operated by TAPP method. Postoperative complications like seroma formation; subcutaneous emphysema was seen in TEP group. Two cases of TEP were converted to TAPP and open lichenstein procedure. Postoperative pain was less in both the group. Patients who underwent TEP procedure spent less time in the hospital compared to those who underwent TAPP procedure. Conclusions: There is no major difference in the outcome after TEP and TAPP surgeries except for some minor complications and the results are comparable in both techniques TAPP and TEP. Both the procedures can be practiced according to surgeon’s familiarity of the procedure.